2014
DOI: 10.1007/s12298-014-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and antinutritional attributes of faba bean (Vicia faba L.) germplasms growing in Bihar, India

Abstract: Eleven germplasms of faba bean seeds from four agroclimatic regions of Bihar, India, have been investigated to estimate their nutritional (soluble protein, free amino acids, starch, reducing and non reducing sugar, total soluble sugar) and antinutritional (total extractable phenol and condensed tannin/proanthocyanidin) parameters. These parameters were found in varying concentration in all genotypes studied. The highest concentration of total extractable phenol and proanthocyanidin (condensed tannin) (2.56 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Total starch content is generally estimated to make up around 40-50% of faba bean seeds (Kozłowska 2001), although more recent studies by Kumar et al (2014) and Ivarsson & Neil (2018) suggest that it is closer to 27-40%. A study investigating starch composition in faba bean found resistant starch to range from 8.1 to 15.0% of total starch, and it has been reported that current faba bean varieties have higher glycaemic index values than other pulse crops (Ambigaipalan et al 2011).…”
Section: Starch and Sugarsmentioning
confidence: 99%
“…Total starch content is generally estimated to make up around 40-50% of faba bean seeds (Kozłowska 2001), although more recent studies by Kumar et al (2014) and Ivarsson & Neil (2018) suggest that it is closer to 27-40%. A study investigating starch composition in faba bean found resistant starch to range from 8.1 to 15.0% of total starch, and it has been reported that current faba bean varieties have higher glycaemic index values than other pulse crops (Ambigaipalan et al 2011).…”
Section: Starch and Sugarsmentioning
confidence: 99%
“…The chemical composition of FB flour was determined and the obtained results are presented in Table 1 Kumar et al (2015). Therefore, FB protein can be used as protein supplement to cereal based foods or can provide a good protein source to produce weaning foods of high nutritive value.…”
Section: Chemical Characteristics Of Faba Beansmentioning
confidence: 99%
“…Faba bean is one of the major crops that consumed worldwide for feeding farm animals (Cazzato et al 2012) and their seeds are high in lysine and arginine, which may complement the low levels in cereals. Faba bean increases humus of soil and use in crop rotation (Kumar et al 2015).…”
Section: Introductionmentioning
confidence: 99%